Odpowiedzi

  • Użytkownik Zadane
2010-02-23T13:15:36+01:00
A) (3a-2b)(a+b)
3a2+3ab-2ab-2b2

b) (x-15)(x-1)
x2-x-15x+15=x2-16x+15

c) (x-y)(2x+3y)
2x2+3xy-2xy-3y2=2x2xy-3y2

d) (2b-5)(3-2b)-(3b+2)=
6b-4b-15+10b-3b-2=
9b-17

  • Użytkownik Zadane
2010-02-23T13:18:20+01:00
A) =3a^2+3ab-2ab-2b^2=3a^2+ab-2b^2
b) =x^2-x-15x+15=x^2-16x+15
c) =2x^2+3xy-2xy-3y^2=2x^2+xy-3y^2
d) =6b-4b^2-15+10b-3b-2=13b-4b^2-17
e) =15a^2b^5-20a^3b^2+12ab^6-16a^2b^3
f) =24a^4-8a^3b-9a^3b+3a^2b^2
Najlepsza Odpowiedź!
2010-02-23T13:19:34+01:00
A)
(3a-2b)(a+b) =
= 3a² + 3ab - 2ab - 2b² =
= 3a² + ab - 2b²

b)
(x-15)(x-1) =
= x² - x - 15x + 15 =
= x² - 16x + 15

c)
(x-y)(2x+3y) =
= 2x² + 3xy - 2xy - 3y² =
= 2x² + xy - 3y²

d)
(2b-5)(3-2b)-(3b+2) =
= 6b - 4b² - 15 + 10b - 3b - 2 =
= 13b - 4b² - 17

e)
(5ab²+4b³)(3ab³-4a²) =
= 15a²b⁵ - 20a³b² + 12ab⁶ - 16a²b³

f)
8a²-3ab)(3a²-ab) =
= 24a⁴ - 8a³b - 9a³b + 3a²b²